Characterization of mechanical, morphological and thermal properties of low density polyethylene nanocomposite using alumina nano-particles as filler - Ngu, Jenney Lim Song (2010)
Nano alumina was produced by using sol-gel method. Alumina was studied by using XRD, FTIR and TEM to confirm the spectroscopy of alumina and size. Ultrasonication was used to disperse the alumina and SDBS was used as surfactant to prevent the re-agglomeration. The processing conditions of LDPE/ alumina blending were studied. The optimum processing conditions was chosen based on tensile tests. The rotor speed during blending affected the dispersion of alumina in LDPE. The rotor speed 80 rpm gave the most consistent tensile properties, suggesting that the dispersion of alumina was good. Samples of 0.5, 1, 2, 3, and 5 wt% of alumina nanocomposite were prepared. Mechanical, thermal, and morphological properties were characterized. The addition of alumina into LDPE enhanced the tensile properties, i.e., tensile strength (34 - 43%) and Young’s modulus (27 - 57%) of LDPE. The tensile fracture surfaces of the nanocomposites were characterized by SEM and confirmed the tensile results. From the flexural analysis, the presence of alumina has insignificant increment on both flexural strength and flexural modulus. Impact strength for notched izod impact test was decreased at the low percentage of alumina loading. Dynamic mechanical analysis performed shown that Tg increased with the increase of alumina loading and damping value decreased with alumina loading. Thermal stability of the nanocomposites was studied by using TGA and no significant difference in stability was observed. Did not show great different of stability. Lastly, the crystallinity of nanocomposites was investigated with DSC. The crystallinity of nanocomposites decreased with the presence of alumina, because alumina restricts the movement of macromolecular chain in LDPE.